Retrieval team-initiated early donor management increases the donor heart utilization rate for transplantation. (18th September 2018) - Barbero, Cristina; Ravaglioli, Antonio; Page, Aravinda A; Betts, Graham A; Fakelman, Stephen M; Pavlushkov, Evgeny; Messer, Simon; Parizkova, Barbora; Berman, Marius; Tsui, Steven
Abstract: OBJECTIVES: Heart transplantation represents the most effective therapy that is currently available for end-stage heart failure. Despite the shortage of organ donors, many donor hearts are not accepted for transplantation due to poor function. Targeted donor management may increase the donor heart utilization rate. The aim of this study is to analyse a 2-year experience of early donor management through the 'scout programme' by a high-volume national cardiothoracic organ retrieval team. METHODS: A prospective cohort study was carried out between 2013 and 2015 on consecutive donation from brain-dead donors. A member of the cardiothoracic retrieval team travelled to the intensive care unit of the donor hospital to assist with early management. RESULTS: One hundred and seventy-eight cardiac donors were enrolled; 106 (59.5%) were 'scouted', and 72 (40.5%) were 'non-scouted'. Donor heart utilization rate in the 'scouted' group was 47.2% (50/106) compared with 30.6% (22/72) in the 'non-scouted' group ( P  = 0.03). On logistic regression analysis, early donor management by the scouts independently predicted donor heart utilization. The time in the operating theatre from donor arrival to skin incision was significantly reduced in the 'scouted' group. No differences were found in the 30-day graft failure rate or the 30-day, 1-year and 2-year survival rates of the recipients between the 2 groups. CONCLUSIONS: Early donor management delivered by the cardiothoracic retrieval team significantly increased the donor heart utilization rate from existing donors. Moreover, the time in the operating theatre from donor heart arrival to skin incision was significantly reduced.